Biopriming with plant growth-promoting microbes enhances growth, yield, and reduces the disease incidence of Fusarium wilt disease in shallots - Nasrullah Nasrullah; Rina Sriwati; Said Mirza Pratama; Virda Zikria; Sugianto Sugianto; Samadi Samadi (Faculty of Agriculture, Universitas Malikussaleh, 2026)
Shallot productivity in Aceh Province remains below the national average, primarily due to low soil fertility, drought stress, and high rainfall that exacerbate disease incidence. Biopriming with plant growth-promoting microbes (PGPM) offers a sustainable strategy to enhance crop performance by establishing early mutualistic interactions during seed germination. This study was conducted from August to November 2024 in Paloh Batee Village, Muara Dua District, Lhokseumawe, using a non-factorial randomized block design with three treatments: biopriming of shallot bulbs with Trichoderma harzianum, Bacillus thuringiensis, and Rhizomax (a consortium of Rhizobium sp., Bacillus polymyxa, and Pseudomonas fluorescens). Growth parameters (plant height at 15, 30, and 45 DAS), bulb traits (number, diameter, fresh and dry weight), and the percentage of plants affected by Fusarium wilt disease. Results indicated that biopriming significantly improved plant height at 15 DAS, bulb number, fresh and dry bulb weight, and reduced disease incidence. The most effective treatment was biopriming with Trichoderma harzianum, which consistently enhanced growth, yield, and the percentage of shallots affected by Fusarium wilt.